Analysis Of Community Branding Communication On Digitaldesa.Id Social Media: Instagram Case Study With A Critical Discourse Analysis Approach - Gumilar, Ade; Harliantara, Harliantara; Prasetyo, Iwan Joko; Farida, Farida; Maella, Nurannafi Farni Syam (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to analyze the brand communication strategy used by Digitaldesa.id on the Instagram platform, focusing on community expression and interaction in social media. The methodology used is critical discourse analysis to understand the narratives and representations created by Digitaldesa.id to build brand identity and image among Instagram users. Data is collected by observing user interactions with content published by Digitaldesa.id and its community. The results of research collected from the Instagram account @digitaldesa.id are that the platform has succeeded in playing an important role in strengthening the DIGIDES brand identity through various informative and inspiring content. Through its focus on education, active interaction, community empowerment, and promotion, this account informs and mobilizes community participation in adopting digital technology at the village level.